2021
DOI: 10.1080/01926187.2021.1972494
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Misinformation Regarding Parental Alienation Theory

Abstract: Misinformation regarding parental alienation theory has been published many times in journals and books since the 1980s. This article discusses a specific example of misinformation, i.e., variations of the statement: Parental alienation theory assumes that the favored parent has caused parental alienation in the child simply because the child refuses to have a relationship with the rejected parent, without identifying or proving alienating behaviors by the preferred parent. This is an unusual phenomenon, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…The first stage of this research identified 40 articles or presentations between 1994 and 2020 in which a PA critic stated some version of the relevant misinformation; also, a few writings by PA scholars that could have been misunderstood or misconstrued to say that some practitioners diagnose PA simply based on the child's contact refusal without specifically identifying ABs by the favored parent. The results from the first stage of this research project—including 40 quotations of misinformation—were reported by Bernet (2021).…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations
“…The first stage of this research identified 40 articles or presentations between 1994 and 2020 in which a PA critic stated some version of the relevant misinformation; also, a few writings by PA scholars that could have been misunderstood or misconstrued to say that some practitioners diagnose PA simply based on the child's contact refusal without specifically identifying ABs by the favored parent. The results from the first stage of this research project—including 40 quotations of misinformation—were reported by Bernet (2021).…”
Section: Methodsmentioning
confidence: 87%
“…The current study greatly expanded the previous research on PA misinformation. Bernet (2021) identified 40 examples of the same misinformation published between 1994 and 2020. The current research identified an additional 54 examples published between 1996 and 2022, for a total of 94 examples of the same misinformation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parental alienation (Bernet, 2021), formerly entitled Parental Alienation Disorder (PAD) (Bernet, 2008) and even before that Parental Alienation Syndrome (PAS), was proposed as an alternative explanation for child sexual abuse allegations in 1985 by the late Richard Gardner (Gardner, 2002), and later asserted in domestic violence and child maltreatment allegations in domestic relations courts, where child custody and visitation are decided in divorce or relationship dissolution (Lorandos & Bernet, 2020). The explanation for the child's resistance or fear of the "alienated parent" is that the "alienating parent" has undertaken overt, covert, and/or unconscious endeavors that result in the child's resistance to or fear of contact with the alienated parent.…”
mentioning
confidence: 99%